Genetic Architecture of Anther Extrusion in Spring and Winter Wheat - Muqaddasi, Quddoos H.; Brassac, Jonathan; Börner, Andreas; Pillen, Klaus; Röder, Marion S. (Frontiers in Plant Science, 2017)
Hybrid wheat breeding is gaining prominence worldwide because it ensures higher and more static yield than conventionally bred varieties. The cleistogamous floral architecture of wheat (Triticum aestivum L.) impedes anthers inside the floret, making it largely an inbreeder. For hybrid seed production, high anther extrusion is needed to promote cross pollination and to ensure a high level of pollen availability for the seed plant. This study, therefore, aimed at the genetic dissection of anther extrusion (AE) in panels of spring (SP) and winter wheat (WP) accessions by genome wide association studies (GWAS). We performed GWAS to identify the SNP markers potentially linked with AE in each panel separately. Phenotypic data were collected for three years for each panel. The average levels of Pearson’s correlation (r) among all years and their best linear unbiased estimates (BLUEs) within both panels were high (r (SP) = 0.75, P <0.0001; r (WP) = 0.72, P <0.0001). Genotypic data (with minimum of 0.05 minor allele frequency applied) included 12,066 and 12,191 SNP markers for SP and WP, respectively. Both genotypes and environment influenced the magnitude of AE. In total, 23 significant (|log10 (P)| >3.0) marker trait associations (MTAs) were detected in both panels (SP = 11; WP = 12). Anther extrusion behaved as a complex trait with significant markers having either favourable or unfavourable additive effects and imparting minor to moderate levels of phenotypic variance (R2 (SP) = 9.75 – 14.24%; R2 (WP) = 9.44 – 16.98%). All mapped significant markers as well as the markers within their significant linkage disequilibrium (r2 ≥0.3) regions were blasted against wheat genome assembly (IWGSC1+popseq) to find the corresponding genes and their high confidence descriptions were retrieved. These genes and their orthologues in Hordeum vulgare, Brachypodium distachyon, Oryza sativa and Sorghum bicolor revealed syntenic genomic regions potentially involved in flowering-related traits. Moreover, the expression data of these genes suggested potential candidates for AE. Our results suggest that the use of significant markers can help to introduce AE in high yielding varieties to increase cross fertilization rates and improve hybrid-seed production in wheat.